2002
DOI: 10.1021/jo026020w
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotrimethylsilane:  A Suitable Reagent for the Synthesis of Chlorohydrin Esters

Abstract: A new methodology for obtaining chlorohydrin esters using a one-pot esterification-chlorination reaction, in which one of the reagents, chlorotrimethylsilane, acts as solvent, is described. The reaction is stereospecific and its regioselectivity depends on the number of carbons between the hydroxyl groups present in the starting material. A mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Afterwards, this compound could react with halogen ions present in the medium through a nucleophilic opening process similar to the one proposed by several authors. 17,[24][25][26][27] Although the detailed catalytic function of ILs is not clear at this stage, the preliminary experimental results showed that bromoesterificaction in ILs is not only possible but also satisfactory. Moreover, polarity and H-bonding capability of the IL could have a big influence in the reaction behavior.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Afterwards, this compound could react with halogen ions present in the medium through a nucleophilic opening process similar to the one proposed by several authors. 17,[24][25][26][27] Although the detailed catalytic function of ILs is not clear at this stage, the preliminary experimental results showed that bromoesterificaction in ILs is not only possible but also satisfactory. Moreover, polarity and H-bonding capability of the IL could have a big influence in the reaction behavior.…”
Section: Resultsmentioning
confidence: 96%
“…The need for similar assistance has already been proposed by several authors to explain similar processes. 17,24,25 A feasible mechanism is outlined in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations